Islamic Essence within the Perspective of Pancasila: A Crucial Imperative for Harmony - Mutia Aulia Rahmi; Meredith Tandon; Amina Intes (Yayasan Adra Karima Hubbi, 2023)
Background. In essence, humans were created as khalifatu fi ardh, created in the best possible form. On this earth, humans need guidance and education in their lives. With this education humans get guidance. The importance of adab in studying in everyday life Purpose. This quantitative study aimed to investigate the preferences of Thai as a foreign language (TFL) learner for ten commonly discussed types of OCF. Specifically, it examined whether these preferences are influenced by four learner variables: proficiency level, first language (L1), foreign language classroom anxiety (FLCA), and foreign language enjoyment (FLE). Method. The purpose of this education is to guide people. Results. Character education can simply be interpreted as forming a person's tabi'at, temperament, character, and personality by instilling noble values, so that these values are ingrained, integrated into the heart, thoughts, speech and actions, and manifest their influence in the reality of life easily, of their own accord, original, and because they are sincere solely because of Allah SWT. Conclusion. From the series of discussions and some of the descriptions above, the manners of learning students and their implications for character education in this study can be concluded that the manners of learning according to Az-Zarnuji are a collection of attitudes and behaviors that must be followed by students in undergoing the learning process.